HUBUNGAN PENGETAHUAN DENGAN PEMANFAATAN PEMERIKSAAN IVA PADA WANITA USIA SUBUR (WUS) DI DESA KREMBUNG KABUPATEN SIDOARJO - Khoirun Nissa; Henry Sudiyanto; Rachmah, Siti (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
The purpose of this study was to determine the relationship between knowledge and the use of IVA examination in women of childbearing age (WUS) in Krembung Village, Sidoarjo Regency. This type of research is quantitative analytic and uses a cross sectional research design. The population in this study were all women of childbearing age (WUS) in Krembung Village, Sidoarjo Regency totaling 713 people. While the sample was taken by Cluster Random Sampling as many as 88 people. Data were collected using a Knowledge Questionnaire about IVA. The data collected was processed by data processing and analyzed using the Pearson correlation test. The results showed that most of the respondents had sufficient knowledge, namely 52 people (59.1%), most of the respondents in using the IVA examination were in the never category, namely 76 people (86.4%). The results of data analysis showed that there was a relationship between knowledge and the use of IVA examinations in women of childbearing age (WUS) in Krembung Village, Sidoarjo Regency (p=0.000). Increasing knowledge of women of childbearing age (WUS) can be done through socialization or counseling to women of childbearing age (WUS) either formally in health services or informally